The biology of germ cell tumors in disorders of sex development. Issue 2 (24th November 2016) - Hersmus, Remko; van Bever, Yolande; Wolffenbuttel, Katja P.; Biermann, Katharina; Cools, Martine; Looijenga, Leendert H.J.
Abstract : Development of a malignant germ cell tumor, i.e., germ cell cancer (GCC) in individuals with disorders of sex development (DSD) depends on a number of (epi‐)genetic factors related to early gonadal‐ and germ cell development, possibly related to genetic susceptibility. Fetal development of germ cells is orchestrated by strict processes involving specification, migration and the development of a proper gonadal niche. In this review we will discuss the early (epi‐)genetic events in normal and aberrant germ cell and gonadal development. Focus will be on the formation of the precursor lesions of GCC in individuals who have DSD. In our view, expression of the different embryonic markers in, and epigenetic profile of the precursor lesions reflects the developmental stage in which these cells are blocked in their maturation. Therefore, these are not a primary pathogenetic driving force. Progression later in life towards a full blown cancer likely depends on additional factors such as a changed endocrine environment in a susceptible individual. Genetic susceptibility is, as evidenced by the presence of specific risk genetic variants (SNPs) in patients with a testicular GCC, related to genes involved in early germ cell and gonadal development. Abstract :